Utilization of services for institutional deliveries in Gorkha District - Paudel, Grish; Yadav, Uday Narayan; Thakuri, Sunil Jung; Singh, Jaya Prasad; Marahatta, Sujan Babu (Journal of Nepal Health Research Council, 2017)
Background: Adequate health services for improving maternal and neonatal health is an important global health issues. Institutional delivery is most important component to address maternal and neonatal issue. Institutional delivery service utilization assures safe birth and minimizes the maternal morbidity and mortality. This study was aimed to assess the utilization of institutional delivery service among the mothers of Gorkha district. Methods: A cross sectional study of 180 mothers having child below 2 years residing in Palungtar municipality was done between March to July 2015. Information was collected by using an interviewer administered semi-structured questionnaire. Chi-square test was used to for data analysis. Results: Of total, 93.3% of the mother gave birth to their current child at health institution. The study variables like age at marriage, knowledge on delivery incentive, long waiting hours at health facility, Information on maternal health before current pregnancy, age at first pregnancy, gestational age at first ANC visit and women knowing differences between home and institutional delivery were independent factors influencing utilization of institutional delivery service. Conclusions: Promotion of information, education and communication on maternal health services and delivery incentives could result in utilization of institutional delivery services. Keywords: Antenatal care; institutional delivery; maternal health